Межъязыковые омонимы в лексико-семантической группе „Религия” (на примере польского и русского языков) - Didenko, Natalya (Studia Rossica Posnaniensia, 2020)
The paper aims to present the types of semantic relations which hold between the interlingual homonyms existing in the semantic field of “people’s spiritual life”. The primary type of the relations among the studied lexical units is exclusion (the presence of a religious component in the semantics of a word of one of the studied languages and the lack of such a component in the other language). Because of the significant number of the examples of this type of relation, the words were divided into three thematic groups: 1) concepts (пассия – pasja), 2) objects (арка – arka), 3) people (лектор – lektor). The relation type of inclusion (with the shared religious semantics, one of the homonyms has an additional meaning related to this area) was observed in a few pairs (катафалк – katafalk). The relation type of overlapping (with the shared religious semantics, each of the homonyms has an additional meaning) in a given lexical field was not identified. No relation of overlapping in a given lexical field and only a few cases of the inclusion relation can prove that the resources of Russian and Polish homonymous words belonging to the religious theme of the Orthodox and Catholic Churches contrast with one another in quite an unobvious way. It is conditioned by both linguistic as well as cultural factors.